Women, Business and the Law 2021 - World Bank (Washington, DC: World Bank, 2021)
Women, Business and the Law 2021 is the seventh in a series of annual studies measuring the laws and regulations that affect women’s economic opportunity in 190 economies. The project presents eight indicators structured around women’s interactions with the law as they move through their lives and careers: Mobility, Workplace, Pay, Marriage, Parenthood, Entrepreneurship, Assets, and Pension. This year’s report updates all indicators as of October 1, 2020 and builds evidence of the links between legal gender equality and women’s economic inclusion. By examining the economic decisions women make throughout their working lives, as well as the pace of reform over the past 50 years, Women, Business and the Law 2021 makes an important contribution to research and policy discussions about the state of women’s economic empowerment. Prepared during a global pandemic that threatens progress toward gender equality, findings on government responses to COVID-19 and pilot research related to childcare and women’s access to justice.